2022
DOI: 10.13057/biodiv/d230426
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Assessing the relationship of Sumatran elephant’s movement (Elephas maximus sumatranus) with vegetation intensity in Kotaagung Utara, Lampung Province, Indonesia using NDVI method

Abstract: Abstract. Bakri S, Monik DT, Setiawan A, Winarno GD. 2022. Short Communication: Assessing the relationship of Sumatran elephant’s movement (Elephas maximus sumatranus) with vegetation intensity in Kotaagung Utara, Lampung Province, Indonesia using NDVI method. Biodiversitas 23: 1920-1928. The Indonesian Elephant Conservation Forum stated that the population of Sumatran elephants (Elephas maximus sumatranus) had decreased dramatically up to 70% in the last 20-30 years due to illegal hunting, land conversion, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…In our study, NDVI was positively correlated with Asian elephant habitat use, indicating a preference for diverse and abundant vegetation. Similar preferences where Asian elephants consistently select dense vegetation with different phenology were reported in the Asian elephant’s range ( Thapa, Kelly & Pradhan, 2019 ; Bakri, Setiawan & Winarno, 2022 ; Amorntiyangkul et al, 2022 ). Several studies reported that elephants favour nutrient-rich lowland forest settings, including riparian forests and mountain valleys ( Hedges et al, 2005 ; Pradhan & Wegge, 2007 ; Rood, Ganie & Nijman, 2010 ).…”
Section: Discussionsupporting
confidence: 61%
“…In our study, NDVI was positively correlated with Asian elephant habitat use, indicating a preference for diverse and abundant vegetation. Similar preferences where Asian elephants consistently select dense vegetation with different phenology were reported in the Asian elephant’s range ( Thapa, Kelly & Pradhan, 2019 ; Bakri, Setiawan & Winarno, 2022 ; Amorntiyangkul et al, 2022 ). Several studies reported that elephants favour nutrient-rich lowland forest settings, including riparian forests and mountain valleys ( Hedges et al, 2005 ; Pradhan & Wegge, 2007 ; Rood, Ganie & Nijman, 2010 ).…”
Section: Discussionsupporting
confidence: 61%
“…According [19] that women's interest is generally lower than men in tourist objects or interests that contain a risk of danger as shown by [20] that WKPN which has one of its advantages in the form of elephant ride interests at elephant training centers or also the interest of elephant riding around the border perimeter around to drive wild elephants back into the forest area. As a wild animal, the elephant is nocturnal animal that normally attack against human or anything else that disturbe the animal [21] According to [22] the gender bias against wild animals often occurs when women are behind men because women are generally less adaptable to violence which risks weak physical defense. On the contrary, our finding shows that men's interests are not significantly different from women's.…”
Section: The Influence Of Gender On Tourist Interestmentioning
confidence: 99%
“…In line with this finding, [14] reported that there are as many as 19% the visitors to WKPN are the civil servant employees. This fact shows that for the domestic visitor segment, this group needs to be the target of various promotions and other strategic planning so that the people of the WKPN buffer-zone area can increase their income and simultaneously reduce forest encroachment [20,21,22].…”
Section: The Influence Of Tourist As Civil Servants On Their Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with Moßbrucker et al (2016), who stated that home range sizes varied between locations, individuals, seasons, and habitat conditions (availability of food, water, and human activity). The availability of optimal resources in a habitat will make the Sumatran elephant not have to move too far to find and water sources (Bakri et al 2022). These conditions will form a narrower and smaller home range area.…”
Section: Composition Of Weekly Home Range Areamentioning
confidence: 99%